Some Observations on The Morphological and Physico-Chemical Aspects of The Sand Dunes in Jodhpur District, Rajasthan - Singh, Surendra; Sharma, B K (Annals of Arid Zone, 2016)
The results of the study conducted in Jodhpur district on the morphological and physico-chemical aspects and also on available micronutrient status of two types of sand dunes, viz., longitudinal and parabolic have been discussed. The morphological characteristics of the longitudinal and parabolic dunes of Jodhpur district such as the height, length, width and slopes vary from 10 to 65 m; 500 to 600 m; 200 to 450 m and 4Â° to 22Â°, respectively. These dunes constitute more than 80% fine sand and their water holding capacity varies from 20.0 to 26.3% while organic carbon varies from 0.03 to 0.13%. Available K2O is medium to high while P2O5 is very low. These dunes are well supplied with Fe, Zn and Cu but are deficient in Mn.